Syntetyczna analiza porównawcza środków trwałych w ujęciu prawa bilansowego i podatkowego - Bąk, Melania (Synthetic Comparative Analysis of Capital Assets in the Formulation of Balance and Tax Law, 2006)
Capital assets are the main component of property assets in economic unit. The paper presents basic aspects of capital assets, among others characteristics, pricing and amortization. In an this context short comparative analysis of capital assets in the formulation of balance and tax law is given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 143-158